2007
DOI: 10.1016/j.dnarep.2007.05.013
|View full text |Cite
|
Sign up to set email alerts
|

X-irradiation of cells on glass slides has a dose doubling impact

Abstract: Immunofluorescence detection of γH2AX foci is a widely used tool to quantify the induction and repair of DNA double-strand breaks induced by ionising radiation. We observed that Xirradiation of mammalian cells exposed on glass slides induced 2-fold higher foci numbers compared to irradiation with γ-rays. Here, we show that the excess γH2AX foci after Xirradiation are produced from secondary radiation particles generated from the irradiation of glass slides. Both 120 kV X-rays and 137 Cs γ-rays induce ~20 γH2AX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 19 publications
5
34
1
Order By: Relevance
“…Here, we investigated a range of doses between 2.5 and 200 mGy and show that the level of initial γ-H2AX and pATM foci at 5 min postirradiation depends linearly on dose, with a yield of ≈20 foci per 1 Gy per cell, similar to the yield obtained in previous studies with much higher doses (28) (Fig. 1C and Fig.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Here, we investigated a range of doses between 2.5 and 200 mGy and show that the level of initial γ-H2AX and pATM foci at 5 min postirradiation depends linearly on dose, with a yield of ≈20 foci per 1 Gy per cell, similar to the yield obtained in previous studies with much higher doses (28) (Fig. 1C and Fig.…”
Section: Resultssupporting
confidence: 61%
“…Thus, foci induction is similar in various mouse tissues and increases linearly with dose from 10 mGy to 1 Gy. The induction yield of about 7 foci per cell per 1 Gy at 10 min post-IR is similar to that of our previous study (34) but substantially lower than the level of 15-20 foci per 1 Gy typically observed for human cells in culture (28). We have previously suggested that this difference may reflect that mouse cells have a 20% lower DNA content than human cells, that additional foci loss can occur during the time necessary to retrieve and fix the organs, and that foci scoring in a cross-section of cells embedded in a tissue sample will significantly underestimate the true foci numbers (34).…”
Section: Pretreatment Of Confluent Primary Human Fibroblasts With H 2supporting
confidence: 65%
See 1 more Smart Citation
“…In all subsequent experiments, we analyzed foci at 15 min post-IR. The maximum number of nine γH2AX foci per photoreceptor is substantially lower than the level of approximately 20 foci per human cell in culture (34). However, other mouse tissues, such as the brain and kidney, with cells of different nuclear architecture and size also exhibit only approximately 10.5 foci per cell, suggesting that the difference with human cells in culture is not a specific phenomenon of photoreceptors (35) (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…X-irradiation was performed at 90 or 120 kV. The increase in dose for cells grown on glass coverslips relative to plastic surfaces was taken into account in the dose assessment (20).…”
Section: Cell Culturementioning
confidence: 99%